Rozwój języka dzieci z FASD warunkowany poziomem funkcji poznawczych - Pawłowska-Jaroń, Halina; Orłowska-Popek, Zdzisława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*74.66px); top: calc(var(–scale-factor)*440.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00154);" role="presentation">The article presents relations between language development and cognitive functions <span dir="ltr" style="left: calc(var(–scale-factor)*75.18px); top: calc(var(–scale-factor)*454.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.04374);" role="presentation">in children with <span dir="ltr" style="left: calc(var(–scale-factor)*144.32px); top: calc(var(–scale-factor)*455.55px); font-size: calc(var(–scale-factor)*8.60px); font-family: serif; transform: scaleX(1.0579);" role="presentation">FASD<span dir="ltr" style="left: calc(var(–scale-factor)*167.07px); top: calc(var(–scale-factor)*454.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03234);" role="presentation">. The authors characterise particular cognitive functions con<span dir="ltr" style="left: calc(var(–scale-factor)*75.19px); top: calc(var(–scale-factor)*468.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01215);" role="presentation">nected with perception, processing and storage of information <span dir="ltr" style="left: calc(var(–scale-factor)*328.52px); top: calc(var(–scale-factor)*468.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00323);" role="presentation">as well as control and <span dir="ltr" style="left: calc(var(–scale-factor)*75.34px); top: calc(var(–scale-factor)*482.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.987123);" role="presentation">self-regulation <span dir="ltr" style="left: calc(var(–scale-factor)*135.47px); top: calc(var(–scale-factor)*482.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.997269);" role="presentation">of behaviour. They write <span dir="ltr" style="left: calc(var(–scale-factor)*236.62px); top: calc(var(–scale-factor)*482.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.985499);" role="presentation">about linguistic knowledge as closely coexist<span dir="ltr" style="left: calc(var(–scale-factor)*75.18px); top: calc(var(–scale-factor)*496.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01289);" role="presentation">ing with other cognitive functions. The authors also emphasise two things. First, the <span dir="ltr" style="left: calc(var(–scale-factor)*75.22px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00348);" role="presentation">fact that the quality <span dir="ltr" style="left: calc(var(–scale-factor)*155.34px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.996523);" role="presentation">of cognitive, social and emotional functioning of a <span dir="ltr" style="left: calc(var(–scale-factor)*359.19px); top: calc(var(–scale-factor)*510.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01645);" role="presentation">child depends <span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0032);" role="presentation">equally on <span dir="ltr" style="left: calc(var(–scale-factor)*120.00px); top: calc(var(–scale-factor)*524.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01737);" role="presentation">the harmonious development of perception, motor, language, mental and<span dir="ltr" style="left: calc(var(–scale-factor)*75.34px); top: calc(var(–scale-factor)*538.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01364);" role="presentation"> social skills, and second: the knowledge of the specificity <span dir="ltr" style="left: calc(var(–scale-factor)*311.75px); top: calc(var(–scale-factor)*538.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00845);" role="presentation">of cognitive development, <span dir="ltr" style="left: calc(var(–scale-factor)*74.93px); top: calc(var(–scale-factor)*552.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00103);" role="presentation">which is reflected in the language development, can be helpful in making a <span dir="ltr" style="left: calc(var(–scale-factor)*377.93px); top: calc(var(–scale-factor)*552.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991001);" role="presentation">diagnosis<span dir="ltr" style="left: calc(var(–scale-factor)*75.34px); top: calc(var(–scale-factor)*566.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02024);" role="presentation"> and preparing a <span dir="ltr" style="left: calc(var(–scale-factor)*141.07px); top: calc(var(–scale-factor)*566.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01201);" role="presentation">therapeutic program for children with <span dir="ltr" style="left: calc(var(–scale-factor)*295.67px); top: calc(var(–scale-factor)*567.55px); font-size: calc(var(–scale-factor)*8.60px); font-family: serif; transform: scaleX(1.05102);" role="presentation">FASD.